An overview of Astrocaryum (Bactridinae, Arecaceae) types from Brazil described by João Barbosa Rodrigues - Lima, Gustavo Pereira; Amorim, Gabriela; de Almeida Jr., Eduardo Bezerra (Phytotaxa, 2024)
João Barbosa Rodrigues, a renowned Brazilian botanist, spent years intensively studying Orchidaceae and Arecaceae and oversaw two important institutions in Brazil: the Museu Botânico do Amazonas and the Jardim Botânico do Rio de Janeiro. However, when it comes to his taxonomic studies, there are controversies about the existence of specimens mentioned in the protologues of his new species. For example, for the palm genus Astrocaryum, several issues have arisen regarding identifying and designating nomenclatural types of the species he described. Different researchers presumed that the entire collection of types was destroyed after the Museu Botânico do Amazonas closed and due to natural disasters, that affected his collections in city of Rio de Janeiro. Thus, in this study we investigated the names of Astrocaryum described by Barbosa Rodrigues. We conducted a comprehensive investigation of Barbosa Rodrigues’ works to determine the origin and current location of the possible nomenclatural types associated with the Astrocaryum species he described. Additionally, we reviewed the designations proposed by Jan Wessels Boer and Sidney Glassman for these species in the previous century. Based on our thorough search, we confirmed the absence of the specimens mentioned in the protologues of these species. Furthermore, we substantiated the typifications made by Wessels Boer and Glassman, which were based on illustrations by Barbosa Rodrigues. Our findings confirm the assignment of six lectotypes and twelve neotypes for Astrocaryum based on the Shenzhen Code.